2011
DOI: 10.1089/met.2011.0026
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a): Genotype–Phenotype Relationship and Impact on Atherogenic Risk

Abstract: In 2010, more than 45 years after the initial discovery of lipoprotein(a) [Lp(a)] by Kare Berg, an European Atherosclerosis Society Consensus Panel recommended screening for elevated Lp(a) in people at moderate to high risk of atherosclerotic cardiovascular disease (CVD). This recommendation was based on extensive epidemiological findings demonstrating a significant association between elevated plasma Lp(a) levels and coronary heart disease, myocardial infarction, and stroke. In addition to those patients cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Both SNPs were associated with coronary disease and, after adjustment for the plasma Lp(a) lipoprotein level, the association between LPA genotypes and CAD are abolished. The mechanism whereby Lp(a) may be particularly atherogenic is through its binding and transportation of phospholipids [28]. However, due to the particle homology with plasminogen a pro-enzyme related to fibrinolysis [29,30].…”
Section: Lipoprotein (A)mentioning
confidence: 99%
“…Both SNPs were associated with coronary disease and, after adjustment for the plasma Lp(a) lipoprotein level, the association between LPA genotypes and CAD are abolished. The mechanism whereby Lp(a) may be particularly atherogenic is through its binding and transportation of phospholipids [28]. However, due to the particle homology with plasminogen a pro-enzyme related to fibrinolysis [29,30].…”
Section: Lipoprotein (A)mentioning
confidence: 99%
“…CVD is currently the preeminent health issue worldwide and signifi cant risk factors include hyperlipidaemia, high serum low-density lipoprotein (LDL) cholesterol and lipoprotein(a) levels, with low high-density (HDL) cholesterol (10)(11)(12). In 2013, the results of a large prospective randomised trial on stroke risks showed the benefi ts of a Mediterranean diet with moderate wine consumption in comparison with a low-fat diet.…”
Section: Introductionmentioning
confidence: 99%
“…First, a meta-analysis which included population-based observational studies has examined the relationship between apo(a) and cardio-and cerebrovascular disease risk 40 . Apo(a) is a heritable modulator of Lp (a) effects and smaller apo(a) isoforms have been convincingly shown to be associated with higher Lp(a) levels 15,[17][18][19][20][21][22] . A significant association between smaller apo(a) isoforms and CHD events compared with larger apo(a) isoforms was described by Erqou et al (RR, 2.08; 95% CI, 1.67 to 8 2.58) 40 .…”
Section: Lp(a) and Cardiometabolic And Vascular Disease: A Unique Insmentioning
confidence: 99%
“…Intriguingly, a large part of the circulating Lp(a) level is heritable, with its genetic components located in the LPA gene responsible for the encoding of apo(a) [17][18][19][20][21][22] . However, Lp (a) concentrations are also dependent on the rate of hepatic apo (a) and apoB 100 secretion 23 .…”
Section: Introductionmentioning
confidence: 99%